2022
DOI: 10.1155/2022/8005848
|View full text |Cite|
|
Sign up to set email alerts
|

Serological Characteristics, Etiological Analysis, and Treatment Prognosis of Children with Congenital Hypothyroidism

Abstract: Objective. The aim of the study is to analyze the serological features, etiology, and prognosis of congenital hypothyroidism (CH) treated with L-thyroxine sodium (L-T4). Methods. A total of 126 CH children in our hospital from June 2015 to January 2020 were selected as the research objects, and L-T4 treatment was given immediately after diagnosis. After diagnosis and 24 months of treatment, laboratory serum thyroid function-related indicators were examined, and thyroid changes were determined by ultrasound. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%